2012
DOI: 10.1073/pnas.1117560109
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Stabilin-2 elevates circulating hyaluronic acid levels and prevents tumor metastasis

Abstract: Hyaluronic acid (HA) has been implicated in the proliferation and metastasis of tumor cells. However, most previous studies were conducted on extracellular matrix or pericellular HA, and the role of circulating HA in vivo has not been studied. HA is rapidly cleared from the bloodstream. The scavenger receptor Stabilin-2 (Stab2) is considered a major clearance receptor for HA. Here we report a dramatic elevation in circulating HA levels in Stab2-deficient mice without any overt phenotype. Surprisingly, the meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
75
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(82 citation statements)
references
References 35 publications
3
75
1
Order By: Relevance
“…Stab2 ibl2 mutants survived throughout embryonic development without defects in either blood or lymphatic vascular systems, which were described previously for stab2 morphants, 50,51 and fertile adults were identified in normal Mendelian ratios (Figure 3d,e). Consistent with the increase in circulating HA levels observed in mouse Stab2 knockouts, 52 a complete loss of fluoHA uptake by SECs was observed in zebrafish stab2 ibl2 mutants, showing a conserved role for stab2 in HA clearance in vertebrates (Figure 3f). Importantly, when either DOPG or DSPC liposomes were injected in stab2 ibl2 mutants, a strong reduction of liposome endocytosis by SECs was observed, offset by an increase in circulating liposome levels and an increase in macrophage uptake (Figure 3g,h).…”
Section: Resultssupporting
confidence: 81%
“…Stab2 ibl2 mutants survived throughout embryonic development without defects in either blood or lymphatic vascular systems, which were described previously for stab2 morphants, 50,51 and fertile adults were identified in normal Mendelian ratios (Figure 3d,e). Consistent with the increase in circulating HA levels observed in mouse Stab2 knockouts, 52 a complete loss of fluoHA uptake by SECs was observed in zebrafish stab2 ibl2 mutants, showing a conserved role for stab2 in HA clearance in vertebrates (Figure 3f). Importantly, when either DOPG or DSPC liposomes were injected in stab2 ibl2 mutants, a strong reduction of liposome endocytosis by SECs was observed, offset by an increase in circulating liposome levels and an increase in macrophage uptake (Figure 3g,h).…”
Section: Resultssupporting
confidence: 81%
“…Interestingly, Hirose et al (2012) reported that inhibition of the scavenger receptor, Stabilin-2, in mice increases circulating HA which does not affect primary tumor size but inhibits tumor metastasis. The increased circulating HA was found to be ~40 kDa in size which did not affect tumor cell proliferation, migration, or invasion (Hirose et al, 2012). This size of HA was not tested in our experiments on EC barrier function.…”
Section: Ha Regulation Of Endothelial Barrier Function During Cancmentioning
confidence: 99%
“…In vitro, expression of Stab2 in cultured cells stimulates the binding and Rac-dependent internalization of apoptotic cells and also stimulates TGFβ production (91). Interestingly, Stab1/Stab2 double knockout mice have shorter lifespans and increased tissue inflammation compared to wild-type mice, although these results likely stem from the loss of hyaluronic acid scavenging mediated by these receptors (95, 96). How Stabilin signaling regulates cytokine expression during efferocytosis is still unclear, although STAB1-mediated engulfment requires the intracellular adaptor protein GULP which has been shown to regulate cytokine production downstream of other receptors including LRP1 (97, 98).…”
Section: Introductionmentioning
confidence: 99%